The Microbiome–Metabolome Response in the Colon of Piglets Under the Status of Weaning Stress - Jiang, Xueyuan; Lu, Naisheng; Zhao, Haichao; Yuan, Hao; Xia, Dong; Lei, Hulong (Frontiers in Microbiology, 2020)
Weaning is stressful for piglets involving nutritional, physiological, and psychological challenges, leading to an increase in the secretion of cortisol, changes in gut microbiome and metabolites, whereas the underlying relationships remain unclear. To elucidate this, fourteen Meishan female piglets were divided into the weaning group and the suckling group at the age of 21 days paired by litter and body weight. After 48 hours of experiment, weaned piglets had lower body weight, but higher salivary cortisol level than that of their suckling litter mates (P < 0.05). The composition of the colonic bacterial community and metabolites were different between the two groups, and the first predominant genus of the suckling and weaned piglets colonic microbiome were Bacteroides and Prevotellaceae-NK3B31 group respectively. The suckling piglets had higher proportions of phylum Bacteroidetes and Lentisphaerae, and genus Bacteroides and Lactobacillus in the colonic microbial community, but lower abundance of genus Prevotellaceae-NK3B31 group than that of the weaned piglets (P < 0.05). Accordingly, there were 15 colonic metabolites differed between the two groups, in which 2 metabolites (phenylacetic acid and phenol) negatively related to the abundant of Lactobacillus genus (P < 0.05), while 9 metabolites (acetic acid, arabitol, benzoic acid, caprylic acid, cholesterol, dihydrocholesterol, galactinol, glucose phenol, phenylacetic acid, and oxamic acid, glycerol, propionic acid) positively associated with the proportion of Prevotellaceae-NK3B31 group genus (P < 0.05). Furthermore, the salivary cortisol level negatively associated with the abundance of phylum Lentisphaerae, but positively associated with the phylum Bacteroidetes and the genus Prevotellaceae-NK3B31 group (P < 0.05) respectively. These results provide us with new insights into the cause of the gut microbiome and stress, and the contributions of gut microbiome in metabolic and physiological regulation in response to weaning stress.